If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(2-x)=4-6(x+2)
We simplify the equation to the form, which is simple to understand
12(2-x)=4-6(x+2)
Reorder the terms in parentheses
+(+24-12x)=4-6*(x+2)
Remove unnecessary parentheses
+24-12x=+4-6+*(+x+2+)
Reorder the terms in parentheses
+24-12x=4+(-6x-12)
Remove unnecessary parentheses
+24-12x=+4-6x-12
We move all terms containing x to the left and all other terms to the right.
-12x+6x=+4-12-24
We simplify left and right side of the equation.
-6x=-32
We divide both sides of the equation by -6 to get x.
x=5.33333333333
| 93+-84= | | 10(1-2(1.5))=-5(2(1.5)-1) | | x-4y=48 | | 3+4y=4a+7 | | 15r+9=96 | | 6p^2+21p= | | 93=-84 | | 7x+3=8x-2 | | r(s+4)+9(s+4)= | | 5z^3+14z^2-24z=0 | | r^4=625 | | 4x-15=4x | | 4x^4-121=0 | | 3(1+6b)+3(6-3b)=21 | | 77-5x=7-9x | | 19x=11x | | 5+6x=25x | | 11x+50=6x+25 | | 2x^3+3x^2-72x-108=0 | | 50C=19N+3 | | 3x=2(x+10) | | 3+n/7=-5 | | 2(0.3r+1)=23-0.1r | | -9+4(x-3)=-4x+3 | | 3(x+3)-sx+7=x+4 | | .04x+.07(12000-x)=720 | | 3g-6(g-8)=32 | | z^2=(z-4)(z+5) | | 1000=40x^2 | | 18-3.8t=7.39-1.9t | | 6x^2+72x+210=0 | | a^5-6a^4+a-6=0 |